A 3D crystal plasticity model for coherency loss during precipitation. (20th July 2018) - Oum, G; Thuinet, L; Legris, A
Abstract: A 3D crystal plasticity model dedicated to coherency loss occurring during precipitation is proposed. It relies on (i) the calculation of an effective stress-free strain resulting from the modification of the stress-free strain of the perfectly coherent precipitate due to the presence of interfacial misfit dislocations and (ii) the propagation of the nucleated dislocations inside the matrix. With this approach, it is possible to estimate separately the importance of each contribution (i) and (ii) on the resulting stress around the precipitate and it is shown that none of them can be neglected to correctly estimate the relaxed stress. Numerical results of the model are compared to experiments in the case of γ hydride precipitation in zirconium and a good agreement is obtained concerning the proportion of coherency stress relieved plastically. This type of model can be easily generalized to incorporate any glide systems and coupled to phase-field models in order to study the effect of coherency loss on microstructure evolution.